2007
DOI: 10.2967/jnumed.107.040816
|View full text |Cite
|
Sign up to set email alerts
|

microPET of Tumor Integrin  v 3 Expression Using 18F-Labeled PEGylated Tetrameric RGD Peptide (18F-FPRGD4)

Abstract: In vivo imaging of a v b 3 expression has important diagnostic and therapeutic applications. Multimeric cyclic RGD peptides are capable of improving the integrin a v b 3 -binding affinity due to the polyvalency effect. Here we report an example of 18 F-labeled tetrameric RGD peptide for PET of a v b 3 expression in both xenograft and spontaneous tumor models. Methods: The tetrameric RGD peptide EfE[c(RGDyK)] 2 g 2 was derived with amino-3,6,9-trioxaundecanoic acid (mini-PEG; PEG is poly(ethylene glycol)) linke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
275
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 194 publications
(292 citation statements)
references
References 32 publications
17
275
0
Order By: Relevance
“…60 Cu-ATSM imaging showed therapy responders had lower tumor-to-normal tissue compared to FDG imaging, while non-responders showed high tumor-to-normal tissue ratios in both [105]. Studies comparing 64 Cu-ATSM with 18 F-FMISO and 18 F-FDG in vivo are also reported. The regional distribution of 18 F-FMISO at 2 h correlates well with the distribution of 64 Cu-ATSM at 10 min or 24 h in 9 L gliosarcoma tumors, whereas a poor correlation existed between 64 Cu-ATSM and 18 F-FDG at 10 min [106].…”
Section: Hypoxia Pet Imagingmentioning
confidence: 96%
See 4 more Smart Citations
“…60 Cu-ATSM imaging showed therapy responders had lower tumor-to-normal tissue compared to FDG imaging, while non-responders showed high tumor-to-normal tissue ratios in both [105]. Studies comparing 64 Cu-ATSM with 18 F-FMISO and 18 F-FDG in vivo are also reported. The regional distribution of 18 F-FMISO at 2 h correlates well with the distribution of 64 Cu-ATSM at 10 min or 24 h in 9 L gliosarcoma tumors, whereas a poor correlation existed between 64 Cu-ATSM and 18 F-FDG at 10 min [106].…”
Section: Hypoxia Pet Imagingmentioning
confidence: 96%
“…However, due to the in vivo stability, cyclic RGD is more favorable than linear RGD and has been well studied by labeling with various radioisotopes [62]. 18 F-Galacto-c(RGDfK), radiolabeled PEGylated RGD peptide, F-18-labeled RGD dimer [63], tetramer [64], Cu-64-labeled tetramer and octamer [65], and Ga-68-labeled cyclic RGD dimers [66,67] are all reported in searching for improved pharmacokinetic behaviors, including better tumor uptake and a prolonged retention pattern (Fig. 3).…”
Section: Tumor Angiogenesis Pet Imagingmentioning
confidence: 99%
See 3 more Smart Citations